Dual approach to averaged values of functions: Advanced formulas - Anh, N. D. (Vietnam Journal of Mechanics, 2012)
Averaged values play major roles in the study of dynamic processes. The use of those values allows transforming varying processes to some constant characteristics that are much easier to be investigated. In order to extend the use of averaged values one may apply the dual approach which suggests a consideration of two different aspects of a problem in question. This short communication proposes new advanced formulas for average values of functions based on the dual conception.